2009
DOI: 10.1001/archpediatrics.2009.61
|View full text |Cite
|
Sign up to set email alerts
|

Audible Television and Decreased Adult Words, Infant Vocalizations, and Conversational Turns

Abstract: To test the hypothesis that audible television is associated with decreased parent and child interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
229
3
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(252 citation statements)
references
References 17 publications
11
229
3
9
Order By: Relevance
“…All three underserved groups discussed television, with mixed views. The evidence (particularly about different types of programmes 244 and the effect for different families and children [245][246][247] ) is unclear regarding the impact of television. This therefore merits further investigation so that appropriate advice is given to families, particularly in homes where the adults are not proficient in English and where the effect of watching television may be differential.…”
Section: Low Socioeconomic Status Groupsmentioning
confidence: 99%
“…All three underserved groups discussed television, with mixed views. The evidence (particularly about different types of programmes 244 and the effect for different families and children [245][246][247] ) is unclear regarding the impact of television. This therefore merits further investigation so that appropriate advice is given to families, particularly in homes where the adults are not proficient in English and where the effect of watching television may be differential.…”
Section: Low Socioeconomic Status Groupsmentioning
confidence: 99%
“…No research exists at this point to know whether a child would find better things to do with his or her time if all screens were turned off, although evidence suggests that the child would hear more adult speech and talk more. 6 Heavy media use is defined as the television being on always or most of the time. Heavy media use may be a sign of parenting style, so one cannot assume that parents will spend developmentally nurturing time with their child with the television off.…”
Section: A Good Use Of Time?mentioning
confidence: 99%
“…In fact, it seems that audible television is associated with decreased parent-child interactions. 6 Although a leading survey of family media use has reported that 40% of parents watch with their child all the time and 28% watch with their child most of the time, parents also report that they avoid co-viewing because their child's media time provides an opportunity for them to do other things. 3 Although there is equal access to media among children of different socioeconomic groups, the amount of media consumption is unequal.…”
Section: Introductionmentioning
confidence: 99%
“…98 There have been no studies to indicate that screen time contributes positively to infant development, 99,100 and there are now 7 studies that have documented possible language delays among children younger than 2 years who are exposed to television or videos. [100][101][102][103][104][105][106][107][108] 4. Pediatricians and other child health professionals should ensure that only nonviolent media choices be provided to patients in outpatient waiting rooms and inpatient settings.…”
Section: Aap Actionmentioning
confidence: 99%